Lithium protects against lipopolysaccharide‐induced cytotoxicity in SH‐SY5Y cells expressing Alzheimer's presenilin 1 mutation by ameliorating calcium dysregulation: Nonhuman/Target identification and validation studies: Other. (7th December 2020) - Sun, Liang; Liang, Ge; Wei, Huafeng
Abstract: Background: Lipopolysaccharide is a crucial mediator of neuroinflammation in sepsis. Neuroinflammation is implicated in normal brain aging and neurodegeneration in various neurodegenerative disorders including Alzheimer's disease. We examined the effect and mechanisms of lithium protection against lipopolysaccharide‐induced cytotoxicity in human neuroblastoma SH‐SY5Y cells expressing familial Alzheimer's disease mutant presenilin‐1 (PS1) and compared to wide type control. Method: Human neuroblastoma SH‐SY5Y cells transfected with human wild type or point mutant PS1 (M146L) were pretreated with lithium chloride (1 mM) for 1 week, and then challenged with lipopolysaccharide for 24 h. Cell viability was determined by the 3‐(4, 5‐dimethylthiazol‐2yl)‐2, 5‐diphenyltetrazolium bromide (MTT) reduction assay. Alterations of cytosolic Ca 2+ concentrations were measured using jellyfish specific photo protein aequorin‐based probes. Result: Lipopolysaccharide resulted in a dose‐dependent cytotoxic effects (starting from the concentration of 400 μg/ml) in both types of cells. Moreover, lipopolysaccharide (400 μg/ml) caused significantly more cytotoxicity in M146L than its corresponding wild type control cells, which could be inhibited significantly by lithium (1 mM) pretreatment. Lipopolysaccharide induced significantly more elevation of peak cytosolic Ca 2+ concentrations in M146L cells than in wide type control cells, which could be abolished by lithium (1 mM) pretreatment. Conclusions: Our results suggest that lithium pretreatment at clinically relevant concentrations could effectively mitigates lipopolysaccharide mediated cytotoxicity, especially in Alzheimer's PS 1 mutated cells, possibly by ameliorating the abnormally elevated cytosolic Ca 2+ concentration.